Teach: An Ethogram-based Method to Observe and Record Teaching Behavior. Issue 3 (August 2017) - Kline, Michelle Ann
Teaching has attracted growing research attention in studies of human and animal behavior as a crucial behavior that coevolved with human cultural capacities. However, the synthesis of data on teaching across species and across human populations has proven elusive because researchers use a variety of definitions and methods to approach the topic. I propose a novel method for the study of teaching behavior to be used across disciplines and populations toward such a synthesis: a teaching ethogram for animal and cross-cultural human research (TEACH). This article compares the results of the TEACH method with interview and time allocation data from the same study populations on Yasawa Island, Fiji. The TEACH method better matches the emic view of teaching as playing a role in children's learning in Fiji, in contrast to the time allocation method. The TEACH method also produces quantitative data with greater behavioral detail than the other methods. This feature is particularly important for the usefulness of the TEACH method in making broad comparative data possible.